Effectiveness of resilience-based interventions in schools for adolescents: a systematic review and meta-analysis - Llistosella, Maria; Goni-Fuste, Blanca; Martín-Delgado, Leandra; Miranda-Mendizabal, Andrea; Franch Martinez, Berta; Pérez-Ventana, Carmen; Castellvi, Pere (Frontiers in Psychology, 2023)
Introduction Resilience has been identified as a dynamic process that provides capabilities to face adversity. Considering the many protective factors involved in resilience and that the school is a key context to promote resilience, this review aimed to examine the effect of school-based interventions on resilience in adolescents. Methods A systematic literature review and meta-analysis were conducted in July 2021 on four databases. The risk of bias was assessed using the Cochrane risk of bias tool. Random-effects meta-analysis was used to obtain pooled estimates. Stratified analyses were done according to population type (general, at risk), intervention type, and follow-up assessments. Results Of the 1,667 articles obtained, 27 were included in the systematic review and 16 in the meta-analysis. The random effects indicated a significant increase in resilience after the intervention [SMD = 0.58, 95% CI (0.29–0.87)]. Subgroup analysis showed effectiveness only in the population at risk [SMD = 1.28, 95% CI (0.53–2.03)] and early adolescence [SMD = 1.28, 95% CI (0.42–2.14), PI (−7.44 to 10.33)]. Multicomponent intervention [SMD = 1.45, 95% CI (0.11–2.80)] and Cognitive Behavioural Therapy (CBT) [SMD = 0.20, 95% CI (0.06–0.34)] demonstrated substantial effectiveness. Significant results were observed within 8-week follow-ups or less [SMD = 1.55, 95% CI (0.61–2.48)]. Discussion These findings provide evidence that multicomponent and CBT interventions increase resilience in early at-risk adolescents only in the short term. Developing resilience interventions is useful in schools exposed to unfavourable socioeconomic contexts. Furthermore, long-term interventions should be redesigned to improve their effectiveness. Systematic review registration PROSPERO [CRD42021277493].